Enhancement of Anaerobic Digestion of Organic Fraction of Municipal Solid Waste by Microwave Pretreatment - Shahriari Zavareh, Haleh (Université d'Ottawa / University of Ottawa, 2011)
This study evaluates the enhancement of anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW) by microwave pretreatment (MW) at high temperatures (115, 145 and 175°C). The highest level of solubilization was achieved at 175ºC, with a supplemental water addition of 30% (SWA30). Pretreatments combining two modalities; MW heating in presence or absence of hydrogen peroxide (H2O2) was also investigated. Biochemical methane potential (BMP) tests were conducted on the whole OFMSW, as well as on the liquid fractions. The whole OFMSW pretreated at 115 and 145 ºC showed little improvement in biogas production over control. When pretreated at 175 ºC, biogas production decreased due to formation of refractory compounds, inhibiting digestion. For the liquid fraction of OFMSW, the effect of pretreatment on the cumulative biogas production (CBP) was more pronounced for supplemental water addition of 20% (SWA20) at 145 ºC. Combining MW and H2O2 modalities did not have a positive impact on OFMSW stabilization and enhanced biogas production. Based on the BMP assay results, the effects of MW pretreatment (145 ºC) on the AD of OFMSW (SWA20) were further evaluated in single and dual stage semi-continuous digesters at hydraulic retention times (HRTs) of 20, 15, 12 and 9 days. Overall, MW pretreatment did not enhance the AD of the whole waste at the HRTs tested. However, the use of a dual stage reactor digesting non pretreated whole OFMSW had the best performance with the shortest HRT of 9 days. Conversely, for free liquid after pretreatment in two stage reactors at 20 day HRT methane production was tripled. In general, the performance of the dual stage digesters surpassed that of the single stage reactors. Cyclic BMP assays indicated that using an appropriate fraction of recycled effluent leachate can be implemented without negatively effecting methanogenic activity and biogas production. Based on the results obtained in this study, digestion of OFMSW by dual stage reactors without pretreatment appears to provide the best potential for waste stabilization in terms of biogas production and yield, process stability and volumetric loading rates.
Keywords: Anaerobic digestion; Organic waste; Microwave; Pretreatment